2020
DOI: 10.35940/ijrte.e6247.018520
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Optimization of Commercial Solar PV and PTC Plants

Abstract:  Abstract: Installation of solar PV arrays at utility scale is gaining popularity nowadays because of the significant reduction in the cost of components as well as the global push towards clean energy. Solar PV plants along with Parabolic Trough Collector Solar thermal plants has the highest potential among the available Renewable Energy (RE) technologies existing in the world. The objective of this paper is to optimize the performance of commercial Solar PV and PTC power plant for a potential location and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
0
0
1
Order By: Relevance
“…Kumar et al (2010) [4] found that sustainable sources of energy are inexpensive, reliable, and environmentally friendly. Baseer et al (2020) [5] also discussed the limitations of non-renewable additives like solar panels and windmills in strengthening sustainable energy sources. To improve efficiency, Baseer et al (2022) [6] al.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al (2010) [4] found that sustainable sources of energy are inexpensive, reliable, and environmentally friendly. Baseer et al (2020) [5] also discussed the limitations of non-renewable additives like solar panels and windmills in strengthening sustainable energy sources. To improve efficiency, Baseer et al (2022) [6] al.…”
Section: Introductionmentioning
confidence: 99%
“…Blok šema solarne elektrane III MODEL SOLARNE ELEKTRANE U PROGRAMSKOM PAKETU SAMDanas su u upotrebi brojni softveri za projektovanje solarnih fotonaponskih sistema. Sistem Advisor Model (SAM) je efikasan besplatni inženjerski alat koji služi za projektovanje i analizu fotonaposnkih sistema, od malih stambenih solarnih elektrana do velikih industrijskih sistema[8]. Softver sadrži bazu podataka sa podacima o fotonaponskim modulima, invertorima, vremenskim parametrima, nivoima zračenja i ostalim podacima koji su neophodni za projektovanje sistema.…”
unclassified